2018
DOI: 10.1111/bju.14604
|View full text |Cite
|
Sign up to set email alerts
|

Penile length is preserved after implant surgery

Abstract: ConclusionsPI surgery does not significantly decrease penile size compared to the preoperative assessment. The outcome was not affected by co-morbidities. The preoperative length and girth correlated well with the immediate postoperative erect penis, although girth was not necessarily comparable in this series of patients measured under anaesthesia. Recording penile dimensions in the clinic and agreeing these with patients' preoperatively may be a way of improving satisfaction levels with this surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…17 Unrealistic expectations and weight gain (excess pre-pubic fat) are additional contributors. 11 No doubt that the best implant size for a certain patient is the best fitting, neither the oversize nor the undersize. One of the most common complaints after MPI is decreased girth.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…17 Unrealistic expectations and weight gain (excess pre-pubic fat) are additional contributors. 11 No doubt that the best implant size for a certain patient is the best fitting, neither the oversize nor the undersize. One of the most common complaints after MPI is decreased girth.…”
Section: Discussionmentioning
confidence: 99%
“…MPP disadvantages discussed were: poorer concealability; reduced girth; relative instability and rigidity compared to IPP. 7 , 8 , 9 , 10 , 12 , 11 , 13 Choosing the type of device was based on the patient's preference.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this later article, although overall satisfaction was quite high, 92% 4脌5 score, this was not correlated with girth and the study included both inflatable and malleable devices. 101 Other articles have described a notable decrease of penile loss in girth of 0.5 to 2.6 cm 96,109 (Table 2). Overall, however, evidence exploring different outcomes between PP types on girth expansion are poor.…”
Section: Satisfaction and Girthmentioning
confidence: 97%
“…95,99 One recently published observational study on 74 patients demonstrated an increase of 3 cm of the stretched penile length when an AMS LGX 700 was implanted, followed by twice daily vacuum device therapy for 6 months. 100 Although most studies suggest an increase in length and patients may also perceive an increase in length, 80,101 the evidence is conflicted with studies also claiming a measurable decrease in length in 12% (15/122) of patients (includes both inflatable and malleable devices, 9 or in length terms, from 0.2 to 3.0 cm). 102,103 Importantly, there are significant numbers of patients (42脌46%) that are dissatisfied with the appearance of their erect penis post-PP insertion 104 (Table 2).…”
Section: Satisfaction and Lengthmentioning
confidence: 99%